Healthcare workers' willingness to work during an influenza pandemic: a systematic review and meta-analysis. - Aoyagi, Yumiko; Beck, Charles R.; Dingwall, Robert; Nguyen-Van-Tam, Jonathan (Wiley, 2015)
To estimate the proportion of healthcare workers (HCWs) willing to work during an influenza pandemic and identify associated risk factors, we undertook a systematic review and meta-analysis compliant with PRISMA guidance. Databases and grey literature were searched to April 2013, and records were screened against protocol eligibility criteria. Data extraction and risk of bias assessments were undertaken using a piloted form. Random-effects meta-analyses estimated (i) pooled proportion of HCWs willing to work and (ii) pooled odds ratios of risk factors associated with willingness to work. Heterogeneity was quantified using the I(2) statistic, and publication bias was assessed using funnel plots and Egger's test. Data were synthesized narratively where meta-analyses were not possible. Forty-three studies met our inclusion criteria. Meta-analysis of the proportion of HCWs willing to work was abandoned due to excessive heterogeneity (I(2) = 99.2%). Narrative synthesis showed study estimates ranged from 23.1% to 95.8% willingness to work, depending on context. Meta-analyses of specific factors showed that male HCWs, physicians and nurses, full-time employment, perceived personal safety, awareness of pandemic risk and clinical knowledge of influenza pandemics, role-specific knowledge, pandemic response training, and confidence in personal skills were statistically significantly associated with increased willingness. Childcare obligations were significantly associated with decreased willingness. HCWs' willingness to work during an influenza pandemic was moderately high, albeit highly variable. Numerous risk factors showed a statistically significant association with willingness to work despite significant heterogeneity between studies. None of the included studies were based on appropriate theoretical constructs of population behaviour.